Chloroplasts preferentially take up ferric-citrate over iron-nicotianamine complexes in Brassica napus - Müller, Brigitta; Kovács, Krisztina; Pham, Hong-Diep; Kavak, Yusuf; Pechoušek, Jiři; Machala, Libor; Zbořil, Radek; Szenthe, Kálmán; Abadía, Javier; Fodor, Ferenc; Klencsár, Zoltán; Solti, Ádám (Planta, 2019)
MAIN CONCLUSION: Fe uptake machinery of chloroplasts prefers to utilise Fe(III)-citrate over Fe-nicotianamine complexes. Iron uptake in chloroplasts is a process of prime importance. Although a few members of their iron transport machinery were identified, the substrate preference of the system is still unknown. Intact chloroplasts of oilseed rape (Brassica napus) were purified and subjected to iron uptake studies using natural and artificial iron complexes. Fe-nicotianamine (NA) complexes were characterised by 5 K, 5 T Mössbauer spectrometry. Expression of components of the chloroplast Fe uptake machinery was also studied. Fe(III)-NA contained a minor paramagnetic Fe(II) component (ca. 9%), a paramagnetic Fe(III) component exhibiting dimeric or oligomeric structure (ca. 20%), and a Fe(III) complex, likely being a monomeric structure, which undergoes slow electronic relaxation at 5 K (ca. 61%). Fe(II)-NA contained more than one similar chemical Fe(II) environment with no sign of Fe(III) components. Chloroplasts preferred Fe(III)-citrate compared to Fe(III)-NA and Fe(II)-NA, but also to Fe(III)-EDTA and Fe(III)-o,o'EDDHA, and the Km value was lower for Fe(III)-citrate than for the Fe-NA complexes. Only the uptake of Fe(III)-citrate was light-dependent. Regarding the components of the chloroplast Fe uptake system, only genes of the reduction-based Fe uptake system showed high expression. Chloroplasts more effectively utilize Fe(III)-citrate, but hardly Fe-NA complexes in Fe uptake.
Keywords: Iron; kyselina azetidinkarboxylová; Real-Time Polymerase Chain Reaction; Transcriptome; Chloroplasts; kvantitativní polymerázová řetězová reakce; Spectroscopy, Mossbauer; Brassica napus; spektroskopie Mossbauerova; transkriptom; železo; chloroplasty; Ferric Compounds; Azetidinecarboxylic Acid; železité sloučeniny